MEMANFAATKAN KAJIAN FONETIK UNTUK PENGEMBANGAN PEMBELAJARAN ILMU TAJWID - Nasution, Ahmad Sayuti Anshari (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
Based on literary studies and empirical experience, this article aims to highlight the scientific facts that Tajwid (science of recitation of Holy Qurʼan) met for change to be noted is subject to measure objectively, bursting capacity of self and non-precision and control, provided that this science that integrates the phonetics. Thus, the Tajwid be more popular if opened up to take advantage of explorations phonology and the science of medicine and anatomy, and other sciences. This article discusses several cases of voice and intonation issues in the science of scientific productions make it a more visible and controlled and subject to the measure if integrated with the Phonetics. DOI: 10.15408/a.v1i2.1140